WACANA BERITA KEKERASAN TERHADAP PEREMPUAN DALAM MEDIA DARING JAMBIMETRO.COM (Analisis Wacana Kritis Perspektif Sara Mills) - Anggia Puteri; Syahrul Ramadhan; Erizal Gani (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this study is to describe how Metrojambi.com as one of the media online reporting cases of violence against women. This research is qualitative research. Techniques of data collection using techniques refer and note assisted by data collection tables. Data analysis was performed with a description of perspective analysis of Sara Mills. Based on the research results, it can be concluded that from news of violence against women in the case of rape in media online Metrojambi.com published from August 2016-October 2018, construct women as subject, not as object of exploitation. However, in its presentation, women are still described as marginal, weak, defenseless and sensitive. Metrojambi.com's online media positions the reader as an ideological subject. The reader is brought to the narrator's position so readers accept it as a reality. Keywords: discourse, news of violence against women, Metrojambi.com, Sara Mills